Multiple Failure Modes，Causes and Prevention of Random Fracture for Hard Tooth Flank Gears - Xiaolu Zhu (Jixie chuandong)
The history and evolution of the random fracture terms，the morphological features，failure examples，causes and preventive measures of various random fracture modes are comprehensively discussed. Contemporary mechanical engineering proposes high speed，heavy load and light weight requirements； what's more the application conditions are more stringent； thus，the gear tooth random fracture has become a common failure mode. For the most commonly used hard tooth flank gears today，the final bending failure of more than 70% of the gears is random fracture. There are multiple failure modes for random fractures. Both the TIFF（Tooth interior fatigue fracture） and TFF（Tooth flank fracture） discussed are typical random fractures. Facing the important objective existence of gear random fracture，it is suggested that designers，manufacturers and relevant experts and scholars of the gear should do further research and analysis of this failure phenomenon，so as to optimize the design and manufacturing，and avoid random gear fracture as much as possible.